Edukasi Toponimi Dalam Pembuatan Papan Nama Gang Sebagai Upaya Pelestarian Asal-Usul Wilayah Di Perumahan Royal Residence 2 RT 28 RW 003 Kelurahan Bumi Ayu Kecamatan Selebar Kota bengkulu - Rama Dhona Helani; Dina Putri Juni Astuti; Rahmat Jumadillah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Toponymy is the study of the origin, meaning, and use of place names as part of a community’s cultural and historical identity. Place names not only function as geographical markers but also represent local history, collective memory, and regional characteristics. However, rapid residential development often causes a decline in public understanding of the historical background and meaning of place names in their environment. This condition was identified in Royal Residence 2 Housing, RT 28 RW 003, Bumi Ayu Village, Selebar District, Bengkulu City, where the name “Gang Kamboja” has long been used by residents but has not been supported by physical markers that strengthen regional identity and preserve local history. This community service program aimed to increase public understanding of toponymy and preserve the origin of the area through the installation of alley name signs. The program employed the Asset-Based Community Development (ABCD) approach, consisting of Discovery, Dream, Design, and Destiny stages. Activities were carried out on June 6, 2026, involving KKN students and community representatives. The results showed that residents gained a better understanding of the historical meaning of Gang Kamboja as part of their local identity. In addition, ten alley name signs, namely Gang Kamboja 1 to Gang Kamboja 10, were successfully produced and installed at strategic locations. The presence of these signs improved location identification, supported environmental organization, facilitated public services, and strengthened awareness of local historical heritage. Therefore, integrating toponymy education with practical environmental management activities can serve as an effective strategy for preserving local identity and regional history in residential communities.